A Strategy for Planned Product Aging in View of Sustainable Development Challenges - Małgorzata Niklewicz-Pijaczyńska (MDPI AG, 2021)
In this paper, the issue of the deliberate aging of products by manufacturers is discussed. Deliberate aging consists in intentionally planning or designing a product with an artificially limited lifetime in order to force consumers to replace it faster. The resulting rapid acceleration of the cycle of obtaining and utilizing consumer goods has serious consequences in the form of negative externalities. For this reason, the conscious aging of products is now recognized as the cause of unjustified consumption, generating huge economic and social costs and leading to the devastation of the natural environment and excessive exploitation of natural resources. Thus, it is in clear contradiction to the model of sustainable development. The aim of this paper was to identify the purchasing attitudes of buyers in the durable goods market. For its implementation, a pilot questionnaire study, which covered a representative group of 354 respondents, was carried out. The results indicate that the factors that influence the purchase of restitution goods depend on the type of product and the consumer’s income. At the same time, about two thirds of the respondents recognized the problem of the deliberate aging of products. In their opinion, the goods produced in the autarkic economy were more durable and their life cycle was much longer. The results obtained require further empirical verification carried out in comparative studies.